(untitled) (Research, Society and Development, 2020)
In this work the complexes Ln(β-dik)3L (where Ln= Nd+3 e Er+3, β-dik= 4,4,4-trifluoro-1-phenyl-1,3-butanedione (Btfa) and L= 1,10-Phenanthroline (Phen) or 2,2’-Bipyridyl (Bipy)), were synthesized from the direct reaction of LnCl3 with β-diketone and the ligands. The purpose was to create new lanthanide complexes with perspectives of use in markers. After the syntheses, the complexes were characterized by Solubility Test, Scanning Electron Microscopy (SEM) and the thermal properties of compounds were studied using Thermogravimetry Analisys (TGA), Differential Scanning Calorimetry (DSC) and Determination of Melting/Decomposition Intervals. Based on the verified properties, the solubility test found that the complexes are not soluble in chloroform and water. The microscope images showed an excellent crystallization of the complexes. The complexes are stable up to 120°C, after this temperature they show a peak in the DSC referring to the fusion and the beginning of decomposition. The values of activation energy suggests the following decreasing order of stability: Er(Btfa)3Phen>Nd(Btfa)3Phen>Er(Btfa)3Bipy>Nd(Btfa)3Bipy.